Biopsychosocial Factors Associated with Postpartum Haemorrhage in Surakarta, Central Java - Dewi, Rizqa Kartika; Budihastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2018)
Background: Postpartum haemorrhage is the primary cause of maternal mortality worldwide. However, studies in Indonesia examining factors associated with postpartum haemorrhage are sparse. The purpose of this study was to examine factors associated with postpartum haemorrhage.Subjects and Method: This was an analytic observational study with a case-control design. The study was conducted at Dr. Moewardi hospital, Surakarta, Central Java, from May 2017 to May 2018. A total sample of 200 postpartum mothers was selected by fixed disease sampling. The dependent variable was postpartum haemorrhage. The independent variables were age, parity, birth space, anaemia, antenatal care, obstetrics history, education, and self-efficacy. The data were collected by questionnaire and analyzed by path analysis on Stata 13.Results:Postpartum haemorrhagewas positively and diretlyassociated with poor obstetric history(b=0.87; 95%CI=-0.03 to 1.79; p=0.059), older age (b=1.86; 95%CI=0.81 to 2.92; p= 0.001), multiparity(b= 1.62; 95%CI=0.08 to 3.15; p=0.038), anemia (b=1.74; 95%CI= 0.83 to 2.66; p<0.001), and narrow birth space (b=-2.51; 95%CI=-3.56 to -1.47; p<0.001). Postpartum haemorrhage was indirectly associated with antenatal care, education, and self-efficacy.Conclusion: Postpartum haemorrhageis positively associated with poor obstetric history, older age, multiparity, anemia, and narrow birth space. Postpartum haemorrhage is indirectly associated with antenatal care, education, and self-efficacyKeywords: postpartum haemorrhage, determinant, path analysisCorrespondence:Rizqa Kartika Dewi. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: rizqakartika@gmail.com.Journal of Maternal and Child Health (2018), 3(3): 207-215https://doi.org/10.26911/thejmch.2018.03.03.05